(3SDGd hLhGH aj GdYQTs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3SFd GdTjN GHf JjejI abjd dg eG bhd SjOfG ai GdYQT gd gh cQi Ce dG s
(3BNQgG (B:s
(3hcGf Gddg GRGO YhfGg GfeG fOYhg HbUO GdYdh Ohf ZjQg ceG aWQfG Ydi Pdc hdgPG jXgQ GdLhGH Yf GdSDGd ef hLhg eJYOOI fLR GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1/5293) s
Keywords: (3GdJhMjO hGdedd hGdfMds